Digital Eco-Systems Third International Conference, OPAALS 2010, Aracujú, Sergipe, Brazil, March 22-23, 2010, Revised Selected Papers - Basile Colugnati, Fernando Antonio; Rodrigues Lopes, Lia Carrari; Almeida Barretto, Saulo Faria (Lecture Notes of the Institute for Computer Sciences, Social Informatics and Telecommunications Engineering,, 2010)
1 The Third International OPAALS Conference was an opportunity to explore and discuss digital ecosystem research issues as well as emerging and future trends in the field. The conference was organized by IPTI - Instituto de Pesquisas em Tecnologia e Inovação (www. ipti. org. br). IPTI is a member of the OPAALS Framework P- gramme 7 Network of Excellence, which is led by the London School of Economics and Political Science. OPAALS is a multi-disciplinary research network of excellence for developing the science and technology behind digital ecosystems. The conference was held within the scope of a broader EU-Brazil bilateral workshop hosted by IPTI in cooperation with the Brazilian government and the European Commission and designed to foster EU support of information and communications technologies (ICT) enablement and socio-economic development in Brazil. The event was held in the city of Aracajú, Sergipe, in the northeast of Brazil, during March 22-23, 2010. Aracajú is the capital of the state of Sergipe and is located on the coast, a tropical region with lush vegetation, rivers and mangroves and an e- nomic landscape dominated by fisheries, tourism and the challenges associated with fostering local economic development in the presence of low ICT penetration. Digital ecosystems (DEs) in some ways represent the next generation of ICT and Internet usage. Applicable to many contexts, they will perhaps have the greatest effect in enabling small and medium-sized enterprises (SMEs) to compete on the global stage.